Development of a compact and robust Polyoxymethylene Dimethyl Ether 3 reaction mechanism for internal combustion engines. (1st April 2019) - Lin, Qinjie; Tay, Kun Lin; Zhou, Dezhi; Yang, Wenming
Highlights: A Polyoxymethylene Dimethyl Ether 3 reaction mechanism is proposed. The proposed mechanism is highly compact (61 species and 190 reactions). The major reaction pathway consists of only 11 species and 17 reactions. Negative temperature coefficient behavior is successfully captured. Well validated against ignition delay, flame speed, species and engine results. Abstract: With high oxygen content, Polyoxymethylene Dimethyl Ether 3 (PODE3 ) is a potential fuel additive to reduce soot emissions. However, reaction mechanisms to describe PODE3 combustion are not yet compact enough for 3-D numerical simulations. Therefore, the current work aims to develop a small yet reliable PODE3 reaction mechanism. Based on sensitivity analysis, the major reaction pathway is identified to construct the PODE3 sub-mechanism. Thereafter, it is integrated with a primary reference fuel (PRF) mechanism to create a PRF-PODE3 mechanism containing 61 species and 190 reactions. The major reaction pathway of the PODE3 sub-mechanism consists of only 11 species and 17 reactions. Furthermore, the new mechanism has been well validated with experimental results in terms of ignition delay times (rapid compression machine at pressures = 1.0 MPa and 1.5 MPa, equivalence ratios = 0.5, 1.0 and 1.5), laminar flame speeds (Pin  = 1 atm, Tin  = 408 K), flame species concentrations (pressure = 33.3 mbar, equivalence ratio = 1) and homogeneous charge compression ignition (HCCI) combustion (equivalence ratios = 0.18 and 0.34). Overall, this highly compact yet robust PRF-PODE3 mechanism is demonstrated to be suitable for internal combustion engine simulations. In addition, with good agreement in terms of fundamental combustion validations, the proposed PRF-PODE3 mechanism can reasonably be applied to other practical applications such as simulations in jet engines, pulse detonation engines, boilers and furnaces.